Environmental performance of shared micromobility and personal alternatives using integrated modal LCA. (April 2021) - de Bortoli, Anne
Highlights: An integrated process-based LCA is conducted on micromobility modes in Paris. Shared e-micromobility ranks between active modes and personal ICE modes. E-micromobility performance is globally driven by the vehicle manufacturing. Ownership does not directly affect the performance, vehicle lifetime mileage does. Assessing the sole carbon footprint leads to biased environmental decision-making. Abstract: The environmental performance of shared micromobility services compared to private alternatives has never been assessed using an integrated modal Life Cycle Assessment (LCA) relying on field data. Such an LCA is conducted on three shared micromobility services in Paris – bikes, second-generation e-scooters, and e-mopeds - and their private alternatives. Global warming potential, primary energy consumption, and the three endpoint damages are calculated. Sensitivity analyses on vehicle lifespan, shipping, servicing distance, and electricity mix are conducted. Electric micromobility ranks between active modes and personal ICE modes. Its impacts are globally driven by the vehicle manufacturing. Ownership does not affect directly the environmental performance: the vehicle lifetime mileage does. Assessing the sole carbon footprint leads to biased environmental decision-making, as it is not correlated to the three damages: multicriteria LCA is mandatory to preserve the planet. Finally, a major change of paradigm is needed to eco-design modern transportation policies.